Dynamic contrast enhanced magnetic resonance imaging: A review of its application in the assessment of placental function. (October 2021) - Jacquier, Mathilde; Arthuis, Chloé; Grévent, David; Bussières, Laurence; Henry, Charline; Millischer-Bellaiche, Anne-Elodie; Mahallati, Houman; Ville, Yves; Siauve, Nathalie; Salomon, Laurent J.
Abstract: It is important to develop a better understanding of placental insufficiency given its role in common maternofetal complications such as preeclampsia and fetal growth restriction. Functional magnetic resonance imaging offers unprecedented techniques for exploring the placenta under both normal and pathological physiological conditions. Dynamic contrast-enhanced magnetic resonance imaging (DCE MRI) is an established and very robust method to investigate the microcirculatory parameters of an organ and more specifically its perfusion. It is currently a gold standard in the physiological and circulatory evaluation of an organ. Its application to the human placenta could enable to access many microcirculatory parameters relevant to the placental function such as organ blood flow, fractional blood volume, and permeability surface area, by the acquisition of serial images, before, during, and after administration of an intravenous contrast agent. Widely used in animal models with gadolinium-based contrast agents, its application to the human placenta could be possible if the safety of contrast agents in pregnancy is established or they are confirmed to not cross the placenta. Highlights: DCE-MRI is a very robust method to investigate the microcirculatory parameters. DCE-MRI provide extraordinary range of data on the placental function. The future of DCE-MRI lies in the widespread availability of safe contrast agents. Perspectives can be envisaged with the combination of several functional-MRI techniques.